1999
DOI: 10.1159/000013494
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Rheumatoid Arthritis Complicated by Myeloperoxidase Antineutrophil Cytoplasmic Antibody-Associated Nephritis

Abstract: We report a myeloperoxidase antineutrophil cytoplasmic antibody-positive rheumatoid arthritis patient who developed necrotizing crescentic glomerulonephritis. Steroid therapy was given combined with an immunosuppressant agent, and double-filtration plasmapheresis was started with the aim of removing antibodies from the blood. This therapeutic regimen was found to be useful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 6 publications
2
9
0
Order By: Relevance
“…MPO-ANCA-associated CrGN in RA patients developed at younger ages than in those without RA. Previous reports also described MPO-ANCA-associated CrGN with RA in middle-aged or younger adults, especially among Japanese (cases 5, 6, 9-11 in Table 3) [4,5,[8][9][10]. Indeed, it is reported that ANCA-associated CrGN mainly affect elderly patients in a Japanese population-based study [21].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…MPO-ANCA-associated CrGN in RA patients developed at younger ages than in those without RA. Previous reports also described MPO-ANCA-associated CrGN with RA in middle-aged or younger adults, especially among Japanese (cases 5, 6, 9-11 in Table 3) [4,5,[8][9][10]. Indeed, it is reported that ANCA-associated CrGN mainly affect elderly patients in a Japanese population-based study [21].…”
Section: Discussionmentioning
confidence: 86%
“…Rheumatoid vasculitis, the most welldocumented form of RA-related vasculitis, develops in RA with clinically active deforming arthritis and extra-articular lesions [2] but rarely involves the kidney [3]. Recently, there have been several case reports on myeloperoxidase antineutrophil cytoplasmic antibody (MPO-ANCA)-associated glomerulonephritis in patients with RA [4][5][6][7][8][9][10], and some specialists consider it to be a form of RA-related complication [6]. However, its clinical features have not been well characterized.…”
Section: Introductionmentioning
confidence: 99%
“…The common renal disorders in patients with RA include amyloid A amyloidosis, membranous nephropathy, mesangial proliferative glomerulonephritis, and drug-induced nephropathy [16]. Although less common, there have been several case reports on MPO-ANCA associated glomerulonephritis in patients with RA [17][18][19][20][21][22][23]. We previously reported that renal dysfunction of MPO-ANCA associated crescentic glomerulonephritis in RA patients showed slower progression compared to typical rapidly progressive glomerulonephritis without RA [8].…”
Section: Discussionmentioning
confidence: 99%
“…7 Recently, p-ANCA-positive crescentic glomerulonephritis has been documented sporadically in RA patients. 8,9 IgA nephropathy is the most common form of glomerulonephritis in the world, 10 and the occurrence of IgA nephropathy has been demonstrated in some patients with RA. 3 However, in such cases, it is difficult to be sure whether primary IgA nephropathy occurs during the course of RA, or secondary IgA nephropathy occurs as a form of RA nephropathy.…”
Section: Discussionmentioning
confidence: 99%